1999
DOI: 10.1074/jbc.274.39.27573
|View full text |Cite
|
Sign up to set email alerts
|

A Relationship between Protein Kinase C Phosphorylation and Calmodulin Binding to the Metabotropic Glutamate Receptor Subtype 7

Abstract: Metabotropic glutamate receptor subtype 7 (mGluR7) is coupled to the inhibitory cyclic AMP cascade and is selectively activated by a glutamate analogue, L-2-amino-4-phosphonobutyrate. Among L-2-amino-4-phosphonobutyrate-sensitive mGluR subtypes, mGluR7 is highly concentrated at the presynaptic terminals and is thought to play an important role in modulation of glutamatergic synaptic transmission by presynaptic inhibition of glutamate release. To gain further insight into the intracellular signaling mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
109
3
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(119 citation statements)
references
References 35 publications
6
109
3
1
Order By: Relevance
“…CaM has been shown to bind to several GPCRs (18)(19)(20)(21)(26)(27)(28), and in some cases, CaM is implicated in the regulation of GPCR trafficking. For example, agonist-induced endocytosis of the 5-HT 1A receptor is prevented by pharmacological inhibitors of CaM (29).…”
Section: Discussionmentioning
confidence: 99%
“…CaM has been shown to bind to several GPCRs (18)(19)(20)(21)(26)(27)(28), and in some cases, CaM is implicated in the regulation of GPCR trafficking. For example, agonist-induced endocytosis of the 5-HT 1A receptor is prevented by pharmacological inhibitors of CaM (29).…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione-S-transferase (GST) Pull-down Assay, Immunoprecipitation, and Yeast Two-hybrid Screening-Protein purification and pulldown assay were performed as described previously (24,30). For pulldown assay, 10 g of GST fusion proteins were immobilized on glutathione-Sepharose 4B beads (25 l) and incubated with either supernatants (100 g) containing recombinant tamalin transiently expressed in COS-7 cells or the purified recombinant thioredoxin fusion proteins (10 g).…”
Section: Methodsmentioning
confidence: 99%
“…For example, a set of postsynaptic density 95/disc-large/zona occludens proteins bind to the SSV motif on the distal C-terminal 5-HT 2C receptor and have a key role in receptor desensitization and internalization after prolonged agonist exposure (Gavarini et al, 2006). The 5-HT 2C receptor C-terminus also interacts with calmodulin (CaM) (Becamel et al, 2002), a ubiquitous modulator of Ca 2ϩ -dependent processes that has been found to interact with many other GPCRs, including the dopamine D 2 , metabotropic glutamate mGlu5 and mGlu7, -opioid, vasopressin V2, angiotensin II AT 1A , and serotonin 5-HT 1A and 5-HT 2A receptors (Minakami et al, 1997;Nakajima et al, 1999;O'Connor et al, 1999;Thomas et al, 1999;Wang et al, 1999;Bofill-Cardona et al, 2000;Nickols et al, 2004;Turner et al, 2004;Turner and Raymond, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the GPCR, CaM interaction with the receptor can affect its coupling with the G protein or its phosphorylation by protein kinase C (Nakajima et al, 1999;O'Connor et al, 1999;Wang et al, 1999;Bofill-Cardona et al, 2000;Turner et al, 2004;Turner and Raymond, 2005), suggesting a possible role in receptor desensitization. CaM can also directly contribute to receptor signaling (Della Rocca et al, 1999;O'Connor et al, 1999;Nickols et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation